2010
DOI: 10.1097/brs.0b013e3181c7c8f6
|View full text |Cite
|
Sign up to set email alerts
|

Major Intraoperative Neurologic Monitoring Deficits in Consecutive Pediatric and Adult Spinal Deformity Patients at One Institution

Abstract: Primary NM scoliosis and revision sagittal plane deformities appear to carry greatest incidence of NMCs during surgical intervention. Most observed NMCs did not result in a permanent neurologic deficit. Neuromonitoring should be assessed throughout the entire surgical procedure. This study may aid surgeons and patients to better assess neurologic risks related to spinal deformity surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 17 publications
0
39
1
Order By: Relevance
“…In their series of 264 patients, 154 were pediatric cases, and the authors reported incidences of neuromonitoring changes and neurological deficit of 4.6% and 1.1%, respectively. 4 Kundnani et al evaluated 354 consecutive adolescent idiopathic scoliosis patients who underwent spinal deformity surgery with IONM. They had 13 true neurophysiological alerts (3.7% of 354 cases), with 2 (0.6%) of those 13 demonstrating postoperative neurological deficits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their series of 264 patients, 154 were pediatric cases, and the authors reported incidences of neuromonitoring changes and neurological deficit of 4.6% and 1.1%, respectively. 4 Kundnani et al evaluated 354 consecutive adolescent idiopathic scoliosis patients who underwent spinal deformity surgery with IONM. They had 13 true neurophysiological alerts (3.7% of 354 cases), with 2 (0.6%) of those 13 demonstrating postoperative neurological deficits.…”
Section: Discussionmentioning
confidence: 99%
“…12 Somatosensory evoked potentials (SSEPs) were the first modality to be widely adopted, and have been routinely employed for over 20 years. 4 SSEPs inform the surgeon about the integrity of afferent information in the dorsal columns of the spinal cord. Some limitations of SSEPs include the delay associated with the signal averaging requirements related to data collection and the fact that the anterior spinal artery does not directly supply the dorsal columns.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These rates are within the range of 0.5 to 3% risk of neurological injury reported in the literature for deformity surgeries. [1][2][3][4][5][6][7] Although the findings from this study may seem to suggest that ION may not influence the rate of neurologic injury, this result must be interpreted with caution as inherently riskier surgeries may utilize neuromonitoring more, leading to an actual reduction in injuries more dramatic than observed in this study. Fu et al reported higher rates of neurologic deficits with ION in pediatric spine cases, which were attributed to the disproportionate use of monitoring in higher risk cases.…”
Section: Discussionmentioning
confidence: 90%
“…In spinal deformity surgery, the risk of neurological injury is estimated to be from 0.5 to 3%. [1][2][3][4][5][6][7] These injuries are thought to occur from implant-related damages, correction maneuvers, or ischemia. 8 To decrease the risk of these adverse events, intraoperative neuromonitoring (ION), such as motor-evoked potential (MEP), somatosensory evoked potential (SSEP), and electromyography (EMG), is used to detect impending injury of neural elements.…”
Section: Introductionmentioning
confidence: 99%